Extractive Policies in Indonesia and Their Impact on the Environment: An Analysis of Environmental Politics and Natural Resource Governance - Ayuni Nur Siami (Universitas Bina Mandiri Gorontalo, 2026)
The extractive sector—especially mining and energy—plays a central role in Indonesia's economy, but it is also a major source of environmental degradation. This article analyses extractive policies in Indonesia and their impact on the environment using a qualitative approach and an environmental political ecology framework. This study aims to evaluate the consistency of extractive policies with the principles of sustainable development and the effectiveness of environmental governance implemented by the state. Data were obtained through literature studies on national regulations, reports of international institutions, and articles from reputable journals. The results of the study show that extractive policies in Indonesia are still oriented toward economic growth and state revenue, with weak integration of environmental protection and community participation. Policy implementation often faces problems of law enforcement, conflicts of interest, and inequality in power relations between the state, corporations, and local communities. This article recommends extractive policy reforms that emphasize the principles of environmental justice, transparency, and accountability as prerequisites for sustainable development.